2019
DOI: 10.1111/2041-210x.13205
|View full text |Cite
|
Sign up to set email alerts
|

MVSE: An R‐package that estimates a climate‐driven mosquito‐borne viral suitability index

Abstract: Viruses, such as dengue, Zika, yellow fever and chikungunya, depend on mosquitoes for transmission. Their epidemics typically present periodic patterns, linked to the underlying mosquito population dynamics, which are known to be driven by natural climate fluctuations. Understanding how climate dictates the timing and potential of viral transmission is essential for preparedness of public health systems and design of control strategies. While various alternative approaches have been proposed to estimate local … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(74 citation statements)
references
References 74 publications
(159 reference statements)
6
68
0
Order By: Relevance
“…We then used the R package MVSE and entomological and epidemiological priors documented in the literature (Supplementary Table 1 ) to calculate daily transmission potential, from which we calculated weekly means for the duration of our study period 17 . We found that the model was reasonably robust to a range of priors for each of the parameters and therefore elected to use short human incubation and infectious period estimates to inform the model.…”
Section: Methodsmentioning
confidence: 99%
“…We then used the R package MVSE and entomological and epidemiological priors documented in the literature (Supplementary Table 1 ) to calculate daily transmission potential, from which we calculated weekly means for the duration of our study period 17 . We found that the model was reasonably robust to a range of priors for each of the parameters and therefore elected to use short human incubation and infectious period estimates to inform the model.…”
Section: Methodsmentioning
confidence: 99%
“…[37]). Mathematical details can be found in our recent publication introducing the theory, practice and free R package that estimates the index P [33].…”
Section: The Suitability Index Pmentioning
confidence: 99%
“…The main results can be reproduced by estimating index P with the freely available Mosquito-borne Viral Suitability Estimator (MVSE) R package (code as provided in Supplementary Text S2 section 3.13 of [33]), using the Israeli meteorological data as input and the priors listed in the Table. The MVSE is freely available at https://sourceforge.net/projects/mvse/. In the Supplement, we include minimal code that estimates the index P from the Israeli meteorological stations included in this study.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations